Structural properties of N-dodecyl-N, N-dimethyl-3-ammonio-1-propane-sulfonate micelle in water by molecular dynamics simulation. Issue 12 (2nd December 2017) - Qu, Guangmiao; Guan, Qi; Pan, Yong; Wang, Mingquan; Li, Jie; Niu, Ruixia; Ding, Wei
ABSTRACT: Here we report a molecular dynamics simulation on the structures of N -dodecyl- N, N -dimethyl-3-ammonio-1-propane-sulfonate (SB12-3) micelle. We tracked the formation of the micelle with 90 SB12-3 molecules forming a spherical-like shape. The estimation of average values of moments of inertia and eccentricity value is being used to prove this. Radial distribution function, hydrogen bond, and the deuterium order parameter ( S CD ) were also used to elucidate the hydrophobic and hydrophilic effects on SB12-3 micelle formation. Radial distribution function and hydrogen bonds indicate the strong interaction of the hydrophilic groups with water molecules. S CD indicates that with the increase of SB12-3 the hydrophobic tail becomes ordered. Carbon atoms of the hydrophobic tail chain pack closely near ; the is "fixed" by the adjacent water molecules and loses the flexibilities together with the hydrophobic tail end atoms. Overall, the obtained results are consistent with the existing experimental findings. GRAPHICAL ABSTRACT: